Dependence of Pedersen conductance in the E and F regions and their ratio on the solar and geomagnetic activities. Issue 3 (6th March 2017) - Sheng, Cheng; Deng, Yue; Lu, Yang; Yue, Xinan
Abstract: Ionospheric conductivity plays an important role in the magnetosphere‐ionosphere coupling. The altitudinal distribution of Pedersen conductivity gives us a rough idea about the altitudinal distribution of Joule heating at high latitudes, which is of great significance regarding the response of upper atmosphere to geomagnetic energy inputs. Based on the electron density profiles derived from the Constellation Observing System for Meteorology, Ionosphere, and Climate measurements during 2009–2014, Pedersen conductivity has been estimated. A climatologic study of the height‐integrated Pedersen conductivity in both E (100–150 km) and F (150–600 km) regions, i.e., Σ P E and Σ P F, and their ratio ( γ P = Σ P E / Σ P F ) under different solar and geomagnetic conditions has been conducted. Both Σ P E and Σ P F increase with F 10.7 and A p indices. Their ratio is smaller at higher solar flux but larger under more disturbed geomagnetic conditions. Meanwhile, an interhemispheric asymmetry has been identified in the A p and F 10.7 dependencies of γ P, which also varies with local time. These results will help to improve our understanding of the variations of the altitudinal energy distribution under different solar and geomagnetic conditions and the interhemispheric asymmetry of the high‐latitude electrodynamics. Key Points: COSMIC derived electron densities are used to estimate the Pedersen conductivity at high latitudes Solar radiation and geomagnetic activity are found to influence the ionospheric Pedersen conductance in different ways E and F region Pedersen conductances and their ratio on the nightside have a larger difference in the postmidnight sector between the two hemispheres